The Influence of Intervertebral Disc Microenvironment on the Biological Behavior of Engrafted Mesenchymal Stem Cells - Jing Zhang; Wentao Zhang; Tianze Sun; Jinzuo Wang; Ying Li; Jing Liu; Zhonghai Li (Stem Cells International)
Intervertebral disc degeneration is the main cause of low back pain. Traditional treatment methods cannot repair degenerated intervertebral disc tissue. The emergence of stem cell therapy makes it possible to regenerate and repair degenerated intervertebral disc tissue. At present, mesenchymal stem cells are the most studied, and different types of mesenchymal stem cells have their own characteristics. However, due to the harsh and complex internal microenvironment of the intervertebral disc, it will affect the biological behaviors of the implanted mesenchymal stem cells, such as viability, proliferation, migration, and chondrogenic differentiation, thereby affecting the therapeutic effect. This review is aimed at summarizing the influence of each intervertebral disc microenvironmental factor on the biological behavior of mesenchymal stem cells, so as to provide new ideas for using tissue engineering technology to assist stem cells to overcome the influence of the microenvironment in the future.